factories the x^2+2x-63
Answers
Answered by
14
Answer :-
____________________________
x² + 2x - 63
= x² + ( 9 - 7 )x - 63
= x² + 9x - 7x - 63
= x ( x + 9 ) - 7 ( x + 9 )
= ( x + 9 ) ( x - 7 ) [ • Required answer ]
________________________
____________________________
x² + 2x - 63
= x² + ( 9 - 7 )x - 63
= x² + 9x - 7x - 63
= x ( x + 9 ) - 7 ( x + 9 )
= ( x + 9 ) ( x - 7 ) [ • Required answer ]
________________________
TheHappySoul:
nyc ❤
Answered by
3
✨ Hey mate here's your answer ✨
I hope this helps you and I am glad to help you with this question.
I hope this helps you and I am glad to help you with this question.
Attachments:
![](https://hi-static.z-dn.net/files/dce/a78c9749142e3e99e70035cec8bb8fba.jpg)
Similar questions